Four palaeonemerteans (Nemertea: Anopla) from a tidal flat in middle Honshu, Japan - Kajihara, Hiroshi (Zootaxa, 2006)
Four species of palaeonemerteans, including Carinina plecta sp. nov., Callinera nishikawai sp. nov., Hubrechtella ijimai comb. nov., and Hubrechtella kimuraorum sp. nov., are described from the Pacific coast of Honshu Island, Japan. The genus Coeia Takakura, 1922 is considered to be a subjective junior synonym of Hubrechtella Bergendal, 1902. Carinina plecta sp. nov. can be distinguished from other congeners by possessing a rhynchocoel wall principally composed of interwoven circular and longitudinal muscle fibres, a condition similar to that in another palaeonemertean genus, Carinoma, as well as certain members in the Hoplonemertea. Callinera nishikawai sp. nov. possesses a remarkable stylet-like apparatus in the proboscis, a feature that has never been reported for any other palaeonemertean. The characteristic ‘tail’ in Hubrechtella (= Coeia) ijimai comb. nov. can be regarded as a heterochronic retention of the structure that appears only in juveniles of other congeners. Hubrechtella kimuraorum sp. nov. has a broad U-shaped blood lacuna in the foregut region before it ramifies into a vascular plexus.